A DIGITAL CERTIFICATION MANAGEMENT MECHANISMS AND SECURITY ROUTING PROTOCOL IN MOBILE AD HOC NETWORK - Ngoc, Luong Thai; Tu, Vo Thanh (Journal of Computer Science and Cybernetics, 2018)
Routing services in Mobile Ad hoc Network (MANET) are the goal of denial of service (DoS) attack forms, such as: Blackhole, Sinkhole, Grayhole, Wormhole, Flooding and Whirlwind. There are some related researches to improve of security performance of routing services, such as H(AODV), OTP_AODV, SAODV and ARAN. They require hypothetical conditions that public key infrastructure (PKI) is available.  TAMAN routing protocol supported a digital certificate verification service adaptively and quickly to the dynamic topology of the network without relying on any certification authorities (CA). However, node's digital certificate is installed manually and TAMAN has not digital certificate provision and revocation mechanisms. Hence, it is restricted to operate on MANET  where nodes move randomly. In this article, we propose a Digital Certification Management Mechanisms (DCMM) based on X.509 standard which supports storing digital certificate, provision and revocation without any PKI. We have implemented DCMM on TAMAN protocol and simulated with NS2 using static and mobility scenarios with speed 30m/s. Simulation results show that digital certificates providing process completely after 70 seconds for 100 member nodes using static scenario and 270 seconds using mobility scenario, and TAMAN performance using DCMM is reduced slightly in terms of packet delivery ratio, end-to-end delay and routing load.